2014
DOI: 10.1016/j.tranon.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

SIX2 Effects on Wilms Tumor Biology

Abstract: Wilms tumor (WT) blastema retains gene expression profiles characteristic of the multipotent nephron progenitor pool, or cap mesenchyme (CM), in the developing kidney. As a result, WT blastema and the CM are believed to represent contextual analogues of one another. Sine oculis homeobox 2 (SIX2) is a transcription factor expressed specifically in the CM, provides a critical mechanism for CM self-renewal, and remains persistently active in WT blastema, although its purpose in this childhood malignancy remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…However, SIX2 levels were not associated with gender, age at diagnosis, and outcome (all P>0.05). Consistent with earlier reports [28], the correlation between tumor tissue and preoperative venous blood with respect to SIX2 methylation was 0.131 (P = 0.228) and 0.451 for SIX2 expression (P=0.004). Correlation between SIX2 hypomethylation and overexpression in WT As shown in Table 3, we observed a significant correlation between SIX2 hypomethylation and overexpression in WT tissue.…”
Section: Msp and Qrt-pcr Analysis Of The Six2 Gene In Wtsupporting
confidence: 91%
See 2 more Smart Citations
“…However, SIX2 levels were not associated with gender, age at diagnosis, and outcome (all P>0.05). Consistent with earlier reports [28], the correlation between tumor tissue and preoperative venous blood with respect to SIX2 methylation was 0.131 (P = 0.228) and 0.451 for SIX2 expression (P=0.004). Correlation between SIX2 hypomethylation and overexpression in WT As shown in Table 3, we observed a significant correlation between SIX2 hypomethylation and overexpression in WT tissue.…”
Section: Msp and Qrt-pcr Analysis Of The Six2 Gene In Wtsupporting
confidence: 91%
“…An earlier study on a specific Wilms' tumor cell line, based on flow cytometry and scratch tests, revealed that overexpression of SIX2 leads to a significant increase in the percentage of cells in the S-phase and enhances cell proliferation and migration [27]. Using a validated model of SIX2 overexpression in a WT cell line, Pierce's research team have observed significantly enhanced cell survival in soft agar and an early effect to increase cell proliferation, shifting the balance in WNT/β-catenin signaling away from a differentiation path and toward a stem cell survival path [28]. Survival and ROC curve analyses disclosed that SIX2 expression is markedly associated with poor outcome, and sensitivity and specificity are significantly increased in diagnosis of short vs. long overall survival in WT children using the SIX2 expression level in preoperative venous blood as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from StarBase prediction confirmed that SIX2 was a potential candidate gene of miR‐335‐5p. As a potent oncogene, SIX2 has previously been demonstrated to accelerate tumorigenesis through regulating the proliferation of tumor cells . Similarly, the higher expression of SIX2 was validated in BC tissues and cells relative to the corresponding controls.…”
Section: Discussionmentioning
confidence: 79%
“…Briefly, using formalin fixed paraffin embedded renal tumor and adjacent kidney specimens collected prospectively and archived in our IRB-approved laboratory embryonal tumor repository, we created two tissue microarrays (TMA) comprised of 148 total punches (~1 mm in diameter each) derived from 32 consecutive childhood WT’s 15 . Serial 5 µm sections of these two TMAs were included for the IHC analysis, which was concentrated on the 32 WT specimens.…”
Section: Methodsmentioning
confidence: 99%